Mechanical Behaviour of Ti6Al4V Lattice Structures Fabricated by Electron Beam Powder Bed Fusion - Huang, Yawen (Auckland University of Technology, 2026)
The development of Additive manufacturing (AM) techniques, such as electron beam powder bed fusion (EBPBF) or electron beam melting (EBM), allows the production of light-weight metallic objects with complex structures, such as lattice structures and cellular porous structures with limited geometrical constrains. In recent years, PBF-fabricated lattice structures with tailored mechanical properties have successfully been designed and manufactured for various applications such as aero engineering and biomedical engineering, as demonstrated in numerous published works. The mechanical properties of the PBF lattices have been extensively investigated considering uniaxial loadings. However, in the real-life applications, the loading can occur in varied directions and the mechanical properties of the PBF lattices can be affected by the different loading directions (LDs). Therefore, the anisotropic mechanical behaviour of the lattice structures must be well understood. Even though published works have confirmed that the mechanical behaviour of PBF lattices structures is affected by the geometrical features, process-induced defects and post-process treatments, limited attention has been given to the effect of LD with respect to the unit cell direction of the lattice. For biomedical implant applications, particularly in hip implants, compressive loading is dominant, thus, this PhD research focuses on investigate the mechanical behaviour of the EBPBF fabricated Ti6Al4V simple-cubic cell based lattice structures under quasi-static and cyclic compressive loadings considering the orientation-dependant effects with respect to the LD. The SC unit cell has been chosen as it can provide a condition for studying the orientation effects without the ambiguity introduced by more complex unit cell geometries. A series of experimental quasi-static and fatigue tests and simulation models were conducted on different EBPBF lattice samples. Three groups of simple-cubic-cell-based lattice structures were produced by EBPBF with unit cell orientations (UCOs) of [001]//LD, [011]//LD and [111]//LD and subject to quasi-static testing and cyclic compressive testing, followed by detailed examinations. In addition, finite element models (FEMs) were conducted to analyse the compressive behaviour of the lattices. The combined effects of LD and UCO on quasi-static and cyclic compressive properties of the lattices have been studied and discussed, providing insight into the anisotropic quasi-static and fatigue behaviour of the lattices. Then an exploratory study has been conducted, porous femoral stem has been designed based on the findings in SC lattices to meet the required fatigue life of 5×10^6 cycles specified the international standard while maintaining the fully porous surface for bone ingrowth. FE simulations and fracture surface analysis has been conducted to identify the effects of stress concentrations and manufacturing defects on the fatigue strength of the produced porous femoral stems. In addition, the effects of surface defects on the fatigue performance of the EBPBF stems have been investigated using Kitagawa-Takahashi approach. It has been found that both the quasi-static and cyclic behaviours of the simple cubic lattices are strongly dependent on their UCOs with respect to the LDs. Among the three groups of lattices, [001]//LD specimens exhibited the most favourable quasi-static compressive strength, with yield strength up to 200% higher and a 4-6 times higher fracture strain than those of the [011]//LD and [111]//LD lattices, due to their less sensitivity to surface defects. Local stress concentrations were found in non-[001]//LD specimens, resulting in yielding and fracturing of these lattices under low loading levels. Considerably greater orientation-dependent effects have been identified in the compressive fatigue behaviour of the lattices, [001]//LD lattices demonstrated approximately 800% higher fatigue strength at 5×10^6 cycles than the non-[001]//LD structures. The low fatigue strength of the non-[001]//LD lattices resulted from crack initiation readily occurring in the high-tension locations, specifically in the top and bottom nodes within each unit cell. The subsequent sideway growth of these cracks leading to fracturing along (001) will be shown. This failure mechanism is absent in [001]//LD lattices resulting in their significantly higher fatigue strength. Examining the data in the literature has revealed that fatigue strength values of all non-SC lattice structures are low, likely due to the same failure mechanism identified for non-[001]//LD SC lattices in this study. The fatigue testing results of the porous femoral stems have suggested that the cracks always initiated at the tension-concentrated zone at lateral side of the stem. With topologically optimised reinforcement, the EBPBF porous stems have successfully met the required fatigue life as specified in the international standard while maintaining sufficient surface porosity for osseointegration. More importantly, the linear-fracture-mechanics-based analysis of surface defects on the EBPBF stems demonstrated that the lack-of-fusion defects on the stress-concentrated locations was the dominant factor contributing to the reduction of the fatigue life of the EBPBF stem components rather than surface roughness.